The art and science of a strategic grantmaker: the experience of the Public Health Agency of Canada’s Innovation Strategy - Bradley Dexter, Shannon; Kavanagh Salmond, Kelly; Payne, Leslie; Chia, Marie C.; Di Ruggiero, Erica; Mahato, Sarah (Canadian Journal of Public Health, 2021)
The Public Health Agency of Canada’s Innovation Strategy (PHAC-IS) was established amid calls for diverse structural funding mechanisms that could support research agendas to inform policy making across multiple levels and jurisdictions. Influenced by a shifting emphasis towards a population health approach and growing interest in social innovation and systems change, the PHAC-IS was created as a national grantmaking program that funded the testing and delivery of promising population health interventions between 2009 and 2020.
Keywords: Canada; Gouvernement du Canada; Réservé UdeM; Santé publique

The art and science of a strategic grantmaker: the experience of the Public Health Agency of Canada’s Innovation Strategy - Bradley Dexter, Shannon; Kavanagh Salmond, Kelly; Payne, Leslie; Chia, Marie C.; Di Ruggiero, Erica; Mahato, Sarah (Canadian Journal of Public Health, 2021)
The Public Health Agency of Canada’s Innovation Strategy (PHAC-IS) was established amid calls for diverse structural funding mechanisms that could support research agendas to inform policy making across multiple levels and jurisdictions. Influenced by a shifting emphasis towards a population health approach and growing interest in social innovation and systems change, the PHAC-IS was created as a national grantmaking program that funded the testing and delivery of promising population health interventions between 2009 and 2020.
Keywords: Canada; Gouvernement du Canada; Réservé UdeM; Santé publique